OASIS—a randomised, placebo-controlled trial of oral glucocorticoids for leg pain in patients with acute sciatica: trial protocol. Issue 6 (23rd June 2020) - Liu, Chang; Abdel Shaheed, Christina; McLachlan, Andrew J; Latimer, Jane; Li, Qiang; Buchbinder, Rachelle; Day, Richard O; Maher, Christopher G; Richards, Bethan; Oliveira, Juliana S; Lin, Chung-Wei Christine
Abstract : Introduction: Sciatica is a lower spine condition characterised by radiating leg pain below the knee. It may be accompanied by motor and sensory loss in the distribution of a spinal nerve. There are few effective treatments for sciatica. Orally administered glucocorticoids have shown some promise, however, any beneficial effects need to be confirmed and weighed against drug safety and cost-effectiveness, in a high-quality, definitive trial. Methods and analysis: The Oral Steroids In Sciatica (OASIS) trial is a randomised, placebo-controlled, double-blind trial that will evaluate a tapering regimen of oral prednisolone in 200 participants with acute sciatica. Participants will be recruited on presentation to general practice, specialist outpatient clinics or hospital emergency departments and randomised to receive orally administered prednisolone 50 mg per day, up to 3 days then tapering to cessation over 10 days, or placebo, for a maximum of 13 days, in addition to guideline advice. Participants will be followed for 1 year. The primary endpoint will be leg pain intensity at 2 weeks. Secondary outcomes will include back pain intensity, disability, time to recovery, quality of life and treatment success rate. Adverse events will be assessed and a cost-effectiveness analysis will be conducted. Ethics and dissemination: Ethical approval has been granted from the Human Research Ethics Committee, The University of Sydney. Trial results will be disseminated by publications and conference presentations and via the media. Trial registration number: ACTRN12619001716156.